Efektifitas Early Warning Score Sistem Untuk Optimalisasi Outcome Pasien dengan Traumatic Brain Injury: A Systematic Review - Syahrul Abdul Yazid; Yulis Setiya Dewi; Herdina Mariyanti (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Traumatic brain injury (TBI) is an acute neurological disease commonly encountered in emergency rooms. Patients with traumatic brain injury face death early in their hospitalization, with mortality remaining high for several years after the injury occurs. Adequate early screening is needed to reduce the mortality rate. Methods: This study used a systematic review design. The articles selected in this study ranged from 2020 to 2025. The search was conducted using four databases: Scopus, PubMed, EBSCO, and ProQuest. The study followed the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) guidelines. Results: Fifteen articles met the inclusion criteria after being evaluated for quality using the JBI Critical Appraisal Tool to determine their suitability for systematic review. Conclusion: This study shows that the use of early detection using the Early Warning Score will improve patient outcomes, even though EWS has several weaknesses when used in patients with traumatic brain injury. Keywords: Early Warning, Traumatic Braim Injury, Mortalitas